The Migration and Growth of a Scientific Learning Community - Shaw, Megan; Kemp, Bob; Sime, Julie-Ann; O’Donoghue, Michael (Proceedings of the International Conference on Networked Learning, 2004)
Early results from a long-term programme of evaluation of the development of the VirRAD online learning community, for the Nuclear Medicine community, are presented. The first results, using a modified version of an extant framework to monitor communication activity show that this has yet to develop, but factors contributing to development have been identified. Results from an additional study provide encouraging predictions of users’ likely acceptance of the community. A relationship between users’ ‘sense of virtual community’ and acceptance has been observed. Recommendations for further work are made in order to confirm the existence and nature of the relationships found.